2013
DOI: 10.1177/1060028013508644
|View full text |Cite
|
Sign up to set email alerts
|

Successful Alteplase Bolus Administration for a Presumed Massive Pulmonary Embolism During Cardiopulmonary Resuscitation

Abstract: The choice of fibrinolytic therapy should be based on hospital availability, with prompt initiation of treatment and incorporation of an intravenous bolus. A reasonable treatment regimen is alteplase 0.6 mg/kg (maximum of 50 mg) or fixed dose of alteplase 50 mg given over 2 to 15 minutes. Resuscitation should be continued for at least 30 minutes, or until ROSC, after fibrinolytic initiation to allow time for the medication to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Among the treatment methods, fibrinolysis has a practical use since it can be applied quickly and easily and is available in most health institutions. In arrest cases, fibrinolytic therapy combined with chest compressions can increase survival by restoring spontaneous circulation 11 . In studies conducted, mortality rates varying between 22% and 90% have been reported after fibrinolytic therapy 9,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the treatment methods, fibrinolysis has a practical use since it can be applied quickly and easily and is available in most health institutions. In arrest cases, fibrinolytic therapy combined with chest compressions can increase survival by restoring spontaneous circulation 11 . In studies conducted, mortality rates varying between 22% and 90% have been reported after fibrinolytic therapy 9,12 .…”
Section: Discussionmentioning
confidence: 99%
“…This was the fastest published administration of rt-PA for PE, although these patients were not in cardiac arrest. Various dosing and infusion times have been studied, but there is a lack of clinical head-to-head studies to definitively say which regimen is best (Prom, Dull, & Delk, 2013). When administering rt-PA for cardiac arrest, it requires prolongation of cardiopulmonary resuscitation (CPR).…”
Section: Cardiac Arrestmentioning
confidence: 99%
“…Two 50-mg doses of alteplase were mixed at the bedside by pharmacy staff in accordance with guideline recommendations and case reports of success improving survival with the use of bolus-dose alteplase therapy during cardiopulmonary resuscitation. 12-14 Each dose was given over 2 minutes and circulated by cardiopulmonary resuscitation for 15 minutes, with return of spontaneous circulation (ROSC) achieved after the second dose was administered. Afterward, pharmacy personnel were consulted for a recommendation regarding anticoagulation therapy after suspected failure of anticoagulation with LMWH.…”
Section: Case Reportmentioning
confidence: 99%